1990
DOI: 10.1185/03007999009112690
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, placebo controlled study of acetyl-l-carnitine in patients with Alzheimer's dementia

Abstract: A randomized, double-blind, placebo-controlled, parallel-group clinical trial was carried out to compare 24-week periods of treatment with 1 g acetyl-l-carnitine twice daily and placebo in the treatment of patients with dementia of the Alzheimer type. A total of 36 patients entered the trial, of whom 20 patients (7 active, 13 placebo) completed the full 24 weeks. Whilst several of the efficacy indices showed little change in either group during the trial, there was an apparent trend for more improvement in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…No placebo group was included and the dose of LAC was smaller than the multiccntcr study (500 mg twice daily). Rai et al [119] found only a trend toward improvement (not statistically significant) on short-term memory tasks in a DBPC study of 20 patients, using 1.000 mg twice daily. Other reports, most of which are subsets of the large Italian trial, have found significant improvement in both depressive symp toms [ 120] and cognitive measures [121,122] using doses of 1.500-2.000 mg per day.…”
Section: L-acetyl Carnitinementioning
confidence: 94%
“…No placebo group was included and the dose of LAC was smaller than the multiccntcr study (500 mg twice daily). Rai et al [119] found only a trend toward improvement (not statistically significant) on short-term memory tasks in a DBPC study of 20 patients, using 1.000 mg twice daily. Other reports, most of which are subsets of the large Italian trial, have found significant improvement in both depressive symp toms [ 120] and cognitive measures [121,122] using doses of 1.500-2.000 mg per day.…”
Section: L-acetyl Carnitinementioning
confidence: 94%
“…Several clinical studies report the beneficial effects of ALCAR or LA:ALCAR administration in a small group of patients with AD that resulted in improved spatial orientation and short-term memory (24,25). LA administration in patients with AD for approximately 1 year also resulted in mild cognitive improvements and stabilization of global neuropsychological test scores (26).…”
mentioning
confidence: 99%
“…We suggest alternative goals for therapy, but are aware that few of them are directly assessed by neuropsychological tests, although some are assessed by rating scales. [35][36][37] Level 1, Class C Lecithin 38,39 Level 1, Class C Arecholine 40 Level 1, Class C Nimodipine 41 Level 1, Class C Velnacrine 42 Level 1, Class D Physostigmine [43][44][45] Level 1, Class D Eptastigmine 46 Level 1, Class D Phosphatidylserine 47 Level 1, Class D Memantine 48 Level 1, Class D 4 Aminopyridine (4AP) 49 Level 1, Class D Naloxone 50 Level 1, Class D Linopirdine 51 Level 1, Class D Aniracetam 52 Level 1, Class D Milacemide 53 Level 1, Class D Nicergolin 54 Level 1, Class D Idebenone 55 Level 1, Class D Huperzine-A 56 Level 1, Class D 5'-methyltetrahydrofolic acid 57 Level 1, Class D Desferrioxamine 58 Level 1, Class D Xantinolnicotinate 59 Level 1, Class D Bespirdine 60 Level 1, Class D Cycloserine 61 Level 1, Class D Cyclandelate 62 Level 1, Class D Thyrotropin 63 Level 1, Class D…”
Section: Discussionmentioning
confidence: 99%